ENHANCING STUDENTS’ SPEAKING SKILLS THROUGH STORYTELLING ON TIKTOK - Assadiyah, Alima; Yuliana, Yohannes Gatot Sutapa; Wardah, Wardah (Journal of Educational Review and Research, 2025)
This study aims to improve the speaking skills of students in class X.10 at SMAN 3 Pontianak by applying storytelling techniques through the use of TikTok. This study was conducted using the Classroom Action Research (CAR) method and involved 34 students as participants. The study was conducted in two cycles, with adjustments made to the implementation based on the difficulties identified in the first cycle to encourage application and adjustment in the second cycle, thus improving the overall results. The results of the study showed a positive impact on students' speaking skills after implementing storytelling activities through TikTok. This improvement was reflected in both the learning process and learning outcomes. Throughout the process, students demonstrate greater focus, enthusiasm, and participation in classroom activities. These results indicate that digital platforms like TikTok can function not only as entertainment tools but also as innovative and relevant media for improving English speaking skills in an educational context.